Sodium-ion battery negative electrode slurry as well as preparation method and application thereof
By using the combination of graphite treated with polar reagents, binder, conductive agent and glue solution in the negative electrode slurry of sodium ion battery, the problem of poor dispersion of the negative electrode slurry in the prior art is solved, and better negative electrode sheet performance and battery performance are achieved.
Patent Information
- Application Number
- CN202411930531.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-11
AI Technical Summary
The dispersion of the negative electrode slurry of existing sodium ion batteries is poor, which affects the performance of the negative electrode sheet.
The negative electrode slurry including binder, conductive agent, glue solution and graphite treated with polar reagents is used to achieve good dispersion of graphite by combining glue solution I and glue solution II.
The dispersion of the negative electrode slurry is improved, the flexibility and battery performance of the negative electrode sheet are improved, the charging window of the battery is expanded, and the internal resistance is reduced.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a sodium ion battery negative electrode slurry and a preparation method and application thereof. Background Art
[0002] Sodium ion battery is a secondary battery (rechargeable battery) that mainly relies on the movement of sodium ions between the positive and negative electrodes to work. Similar to the working principle of sodium ion batteries, it mainly relies on the movement of sodium ions between the positive and negative electrodes to work. The negative electrode of a sodium ion battery usually includes a negative electrode current collector and a negative electrode active layer, of which a graphite negative electrode active layer is one of the common types of active layers. However, the current preparation of the negative electrode slurry for sodium ion batteries has poor dispersibility, which to some extent affects the performance of the negative electrode sheet. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a sodium ion battery negative electrode slurry with good dispersibility. When used in the preparation of the sodium ion battery negative electrode, the battery performance is good.
[0004] The invention also provides a method for preparing negative electrode slurry for a sodium ion battery.
[0005] The invention also provides a negative electrode active layer.
[0006] The invention also provides a negative electrode.
[0007] The invention also provides a sodium ion battery.
[0008] In a first aspect of the present invention, a negative electrode slurry for a sodium ion battery is provided, comprising a binder, a conductive agent, a glue and graphite treated with a polar reagent, wherein the glue comprises glue I and glue II having different viscosities and both containing carboxymethyl cellulose.
[0009] The negative electrode slurry according to the embodiment of the present invention has at least the following beneficial effects:
[0010] The graphite in the negative electrode slurry of the present invention is treated with polar reagents (such as N-methylpyrrolidone and / or alcohol reagents), which can form hydrogen bonds and van der Waals forces to interact with graphite, thereby changing the charge distribution on the graphite surface, increasing its conductivity, and using it in sodium ion batteries to improve the battery charging window and reduce the battery's internal resistance. At the same time, by combining glue liquid I and glue liquid II with different viscosities, the electrostatic repulsion between the glue liquids is used to achieve the purpose of graphite dispersion, the graphite has good dispersibility in the negative electrode slurry, the obtained negative electrode sheet has good flexibility, and the battery performance used is good.
[0011] In some embodiments of the present invention, the viscosity of the glue solution I is 500 to 4000 mPa·s.
[0012] In some embodiments of the present invention, the viscosity of the glue II is 7000-13000 mPa·s.
[0013] In some embodiments of the present invention, the viscosity of the glue solution I is 1000-3500 mPa·s, and the viscosity of the glue solution II is 8000-12000 mPa·s.
[0014] In some embodiments of the present invention, the degree of substitution Da of carboxymethyl cellulose in the glue solution I and the degree of substitution Db of carboxymethyl cellulose in the glue solution II satisfy: Db=Da+0.3.
[0015] In some embodiments of the present invention, the degree of substitution Da of carboxymethyl cellulose in the glue solution I is 0.6 to 0.8, such as 0.60 to 0.80.
[0016] In some embodiments of the present invention, the degree of substitution Db of the carboxymethyl cellulose in the glue II is 0.8 to 1.2, such as 0.80 to 1.20.
[0017] Through the above implementation, carboxymethyl cellulose (CMC) with a low degree of substitution has better lipophilicity, has fewer polar functional groups on its surface, is more likely to be graphite-philic and infiltrate with graphite, and exhibits better bonding force.
[0018] In the present invention, by using a combination of high- and low-substituted carboxymethyl cellulose, the glue has a better coating on the graphite, and the electrostatic repulsion between the CMCs will be stronger, thereby achieving the purpose of dispersing the slurry, making the slurry more evenly dispersed, the particle size refined, and the electrode quality rate improved.
[0019] In some embodiments of the present invention, in the negative electrode slurry, the mass ratio of the glue solution I to the glue solution II is (3-7):(3-7).
[0020] In some embodiments of the present invention, the mass fraction of carboxymethyl cellulose contained in the glue solution I is 1.5% to 3.5%, such as 1.9% to 2.4%.
[0021] In some embodiments of the present invention, the mass fraction of carboxymethyl cellulose contained in the glue solution II is 0.5% to 1.4%, such as 0.8% to 1.2%.
[0022] In some embodiments of the present invention, in the negative electrode slurry, the weight ratio of graphite to carboxymethyl cellulose is (85-99):(0.1-3).
[0023] In some embodiments of the present invention, the polar reagent includes at least one of N-methylpyrrolidone and an alcohol reagent.
[0024] Specifically, alcohols are water-oil amphiphilic substances. The graphite surface is mainly composed of hydrophobic groups. The coating of graphite by alcohols can produce hydrogen bonds and other forces with the graphite surface, affecting the distribution of surface charge on the graphite. On the other hand, the hydrophilic nature of alcohols promotes the coating of the glue, allowing it to be better dispersed in the slurry.
[0025] In some embodiments of the present invention, the polar reagent includes at least one of methanol, ethanol, propanol, butanol, pentanol or hexanol.
[0026] In some embodiments of the present invention, the step of treating the graphite includes: mixing the graphite with a treatment solution containing a polar reagent to obtain the treated graphite.
[0027] In some embodiments of the present invention, the treatment solution includes an aqueous solution of a polar reagent, such as an ethanol aqueous solution.
[0028] In some embodiments of the present invention, the ratio of the mass of the treatment solution to the mass of the graphite is (0.05-0.5):100, such as optionally (0.1-0.15):100.
[0029] In some embodiments of the present invention, in the treatment solution, the concentration of the polar reagent is 0.01 to 0.5 mol / L, such as 0.02 to 0.05 mol / L.
[0030] In some embodiments of the present invention, the step of treating the graphite includes: mixing the graphite with a treatment solution containing a polar reagent to obtain the treated graphite, wherein the stirring time is 5 to 30 minutes and the stirring speed is 100 to 500 rpm.
[0031] In some embodiments of the present invention, the glue solution I is prepared by a preparation method comprising the following steps:
[0032] Sa-1, mixing the fiber and an alcohol solvent, and mixing with an alkaline solution to obtain an alkalized fiber solution;
[0033] Sa-2, the alkalized fiber solution is mixed with chloroacetic acid, and the etherification reaction is carried out at 30-42°C for 10-25 minutes to obtain a glue solution I containing carboxymethyl cellulose.
[0034] In some embodiments of the present invention, step Sa-2 includes: mixing the alkalized fiber solution with chloroacetic acid, performing an etherification reaction at 30-42° C. for 10-25 minutes to generate carboxymethyl cellulose, and adding solvent water to the obtained glue system to obtain glue I containing carboxymethyl cellulose.
[0035] In some embodiments of the present invention, the glue II is prepared by a preparation method comprising the following steps:
[0036] Sb-1, mixing the fiber and an alcohol solvent, and mixing with an alkaline solution to obtain an alkalized fiber solution;
[0037] Sb-2, the alkalized fiber solution is mixed with chloroacetic acid, and the etherification reaction is carried out at 52-60°C for 30-60 minutes to obtain a glue solution II containing carboxymethyl cellulose.
[0038] In some embodiments of the present invention, step Sb-2 includes: mixing the alkalized fiber solution with chloroacetic acid, performing an etherification reaction at 52-60° C. for 30-60 minutes to generate carboxymethyl cellulose, and adding solvent water to the obtained glue system to obtain glue II containing carboxymethyl cellulose.
[0039] In some embodiments of the present invention, in step Sa-1 and / or step Sb-1, the alcohol solvent includes ethanol.
[0040] In some embodiments of the present invention, in step Sa-1 and / or step Sb-1, the mass ratio of the fiber to the alcohol solvent is (0.01-2):1.
[0041] In some embodiments of the present invention, in step Sa-1 and / or step Sb-1, the alkaline solution comprises a NaOH solution. Optionally, the concentration of NaOH in the NaOH solution is 0.2 to 3 mol / L.
[0042] In some embodiments of the present invention, in step Sa-1 and / or step Sb-1, the mass ratio of the fiber to the alkaline solution is (0.01-2):2.
[0043] In some embodiments of the present invention, in step Sa-1 and / or step Sb-1, the fiber and an alcohol solvent are mixed, immersed at 40-50° C. for 0.5-5 h, an alkaline solution is added, and the mixture is reacted at 40-50° C. for 10-60 min to obtain an alkalized fiber solution.
[0044] In some embodiments of the present invention, in step Sa-2 and / or step Sb-2, the mass ratio of the alkalized fiber solution to chloroacetic acid is 1:(0.5-7).
[0045] In some embodiments of the present invention, the adhesive comprises a high-viscosity adhesive, and the viscosity of the high-viscosity adhesive is 30,000 to 80,000 mPa.s.
[0046] In some embodiments of the present invention, the high-viscosity adhesive comprises a high-viscosity adhesive obtained by grafting and modifying polyethylene oxide (PEO). The high-viscosity adhesive is grafted and modified by PEO, and is softer on the pole piece than conventional adhesives such as polyacrylic acid.
[0047] In some embodiments of the present invention, the modified mass ratio of polyethylene oxide (PEO) in the high-viscosity adhesive is 2% to 5%.
[0048] In some embodiments of the present invention, the molecular weight of the high viscosity binder is 20W-40W.
[0049] In some embodiments of the present invention, the elongation at break of the high-viscosity adhesive is 70% to 120%.
[0050] In some embodiments of the present invention, the high viscosity adhesive is prepared by a preparation method comprising the following steps:
[0051] S0, heat the acrylic acid aqueous solution, add the initiator solution, react, then add polyethylene oxide, stir, and obtain a high-viscosity adhesive.
[0052] In some embodiments of the present invention, in the acrylic acid aqueous solution, the ratio of acrylic acid to water is (100-140) mg:12 mL.
[0053] In some embodiments of the present invention, in step S0, the heating temperature is 40-55° C., and the heating time is 0.5-4 h.
[0054] In some embodiments of the present invention, in step S0, the mass ratio of the acrylic acid aqueous solution to the initiator solution is (10-16):1.
[0055] In some embodiments of the present invention, in step S0, the concentration of the initiator in the initiator solution is 0.2-3 mol / L.
[0056] In some embodiments of the present invention, in step S0, the reaction time is 0.5 to 5 hours.
[0057] In some embodiments of the present invention, in step S0, the molecular weight of polyethylene oxide is 3W to 15W.
[0058] In some embodiments of the present invention, in the negative electrode slurry, the mass fraction of the high viscosity binder is 0.1% to 20%, such as 5% to 20%.
[0059] In some embodiments of the present invention, the adhesive further comprises adhesive I. Optionally, the adhesive I includes but is not limited to styrene-butadiene rubber and the like.
[0060] In some embodiments of the present invention, the negative electrode slurry further includes a conductive agent.
[0061] In some embodiments of the present invention, the conductive agent includes but is not limited to one or more of carbon black, acetylene black, carbon nanotubes, graphene, etc.
[0062] In some embodiments of the present invention, the negative electrode slurry includes the following components, measured by weight: 92-96 parts of graphite, 1-3 parts of conductive agent, 1-3 parts of high viscosity binder, and 0.3-3 parts of carboxymethyl cellulose.
[0063] In some embodiments of the present invention, the negative electrode slurry includes the following components by weight: 92-96 parts of graphite, 1-3 parts of conductive agent, 1-3 parts of high viscosity binder, 1-3 parts of binder I, and 0.3-3 parts of carboxymethyl cellulose.
[0064] In some embodiments of the present invention, the D 50 Particle size slurry D 50 And the particle size of graphite graphite D 99 Graphite D 50 The relationship is satisfied: slurry D 50 ≤(graphite D 99 +Graphite D 50 ) / 2.
[0065] Through the above implementation, the negative electrode slurry has better dispersibility, the conductive agent and other components are dispersed more evenly, the negative electrode obtained by slurry coating is less likely to have defects such as particles and pits, has a high quality rate, and is less likely to experience cycle dives.
[0066] In some embodiments of the present invention, the slurry D 50 It is 12.1~12.6μm.
[0067] In some embodiments of the present invention, the graphite D 99 It is 26.8~27.4μm.
[0068] In some embodiments of the present invention, the graphite D 50 It is 12.1~12.7μm.
[0069] In some embodiments of the present invention, the solid content of the negative electrode slurry is 30% to 65%.
[0070] In a second aspect of the present invention, a method for preparing a negative electrode slurry for a sodium ion battery is provided, comprising the following steps:
[0071] S1, mixing raw graphite with a treatment solution containing a polar reagent to obtain a treated graphite slurry;
[0072] S2, mixing the graphite slurry with a conductive agent, a glue, and a binder to obtain a negative electrode slurry for a sodium ion battery.
[0073] In some embodiments of the present invention, in step S1, the treatment solution includes an aqueous solution containing a polar reagent.
[0074] In some embodiments of the present invention, in step S1, the mass ratio of the treatment solution to graphite is (0.05-0.5):100, such as (0.1-0.15):100, and specifically 0.1:100.
[0075] In some embodiments of the present invention, in the treatment solution, the concentration of the polar reagent is 0.01 to 0.5 mol / L, such as 0.02 to 0.05 mol / L.
[0076] In some embodiments of the present invention, in step S1, a portion of the graphite is mixed with the treatment solution, and then the remaining portion of the graphite is added and stirred to obtain the treated graphite slurry.
[0077] In some embodiments of the present invention, step S2 includes mixing graphite slurry with a conductive agent and glue solution I, stirring, and then adding glue solution II and a binder, stirring to obtain the negative electrode slurry.
[0078] In some embodiments of the present invention, in step S2, the graphite slurry is mixed with the conductive agent, the glue liquid I and water, stirred at a speed of 100 to 500 rpm for 0.5 to 3 h, and then the glue liquid II and the high viscosity binder are added, stirred at a speed of 100 to 500 rpm for 0.1 to 2 h, and the binder I is added and dispersed at a speed of 100 to 500 rpm for 0.1 to 2 h to obtain the negative electrode slurry.
[0079] The third aspect of the present invention provides a sodium ion battery negative electrode active layer, which is prepared using the above-mentioned sodium ion negative electrode slurry.
[0080] In some embodiments of the present invention, the thickness of the negative electrode active layer is 130-150 μm.
[0081] In a fourth aspect of the present invention, a sodium ion battery negative electrode sheet is provided, comprising the above-mentioned sodium ion battery negative electrode active layer.
[0082] In a fifth aspect of the present invention, a sodium ion battery is provided, comprising the above-mentioned sodium ion battery negative electrode plate. DETAILED DESCRIPTION
[0083] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0084] The experimental methods without specific conditions in the following examples and comparative examples are generally based on conventional conditions in the art or conditions recommended by the manufacturers; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents available from commercial channels such as conventional markets.
[0085] The fiber in Example 1 is natural cellulose, i.e. cotton;
[0086] The conductive agent is carbon black, with a tap density of 160g / cm 3 , specific surface area 60m 2 / g;
[0087] PEO: molecular weight 5~5.5W;
[0088] Commercial SBR is a styrene-butadiene rubber emulsion with a viscosity of 20-100 mPa.s and a solid content of 40%;
[0089] Example 1
[0090] This embodiment discloses a sodium ion battery negative electrode slurry, the preparation process of which includes the following steps:
[0091] (I) Preparation of glue solution I, glue solution II and high viscosity adhesive:
[0092] Preparation of glue solution I:
[0093] 1) Alkalization: 0.5 kg of fiber was first mixed with 1 kg of ethanol, and soaked at 45° C. for 2 h. Then, 2 kg of 1 mol / L NaOH aqueous solution was added and reacted at 45° C. for 30 min to obtain an alkaline fiber solution.
[0094] 2) Etherification: 0.5 kg of chloroacetic acid was mixed with the alkaline cellulose solution, and the mixture was reacted at 40° C. for 15 min to carry out an etherification reaction to generate carboxymethyl cellulose. Solvent water was added to the obtained glue system to obtain glue solution I; wherein the mass fraction of carboxymethyl cellulose in glue solution I was 2.1%, the degree of substitution Da of carboxymethyl cellulose was 0.65, and the viscosity was 2000 mPa.s.
[0095] Preparation of glue solution II:
[0096] 1) Alkalization: 0.5 kg of fiber was first mixed with 1 kg of ethanol, and soaked at 45° C. for 2 h. Then, 2 kg of 1 mol / L NaOH aqueous solution was added and reacted at 45° C. for 30 min to obtain an alkaline fiber solution.
[0097] 2) Etherification: 0.5 kg of chloroacetic acid was mixed with the alkaline cellulose solution, and the mixture was reacted at 55° C. for 45 min to carry out an etherification reaction to generate carboxymethyl cellulose. Solvent water was added to the obtained glue system to obtain glue II; wherein the mass fraction of carboxymethyl cellulose in glue II was 1%, the degree of substitution Db of carboxymethyl cellulose was 0.95, and the viscosity was 9000 mPa.s.
[0098] Preparation of high-viscosity adhesive: 120 mg of acrylic acid was weighed and added to 12 mL of deionized water, heated in a water bath at 50°C and magnetically stirred at 1000 rpm for 2 h to dissolve and obtain 10 g / L acrylic acid solution A. Then 10 mg of 1 mol / L sodium persulfate aqueous solution was added as an initiator, reacted for 2 h, and then 5 mg of PEO was added and stirred for 30 min to obtain a high-viscosity adhesive (the molecular weight of the high-viscosity adhesive was 35 W, the PEO modification mass ratio was 3%, and the viscosity was 6 W mpa.s).
[0099] (II) Preparation of negative electrode slurry: The negative electrode slurry is prepared according to the following weight proportions: 95 parts of graphite, 1.5 parts of conductive agent, 0.8 parts of carboxymethyl cellulose, 1.2 parts of high viscosity binder, and 1.5 parts of commercial SBR, wherein the mass ratio of glue solution I to glue solution II is 5:5, and specifically comprises the following steps:
[0100] Stirring steps: first add half of the graphite to the stirring tank, add 0.1% of the total mass of the graphite in an ethanol aqueous solution (the concentration of ethanol in the ethanol aqueous solution is 0.03 mol / L), then add the remaining graphite, premix for 15 minutes, set the speed to 200 rpm, and obtain a mixture A; then add the conductive agent, glue solution I and an appropriate amount of water, stir for 1 hour, set the speed to 200 rpm, and obtain a mixture B;
[0101] Dispersion step: Add glue II, high viscosity binder, and appropriate amount of water to mixed material B, stir at 500rpm for 30min to obtain mixed material C, and finally add commercial SBR solution, stir at 200rpm for 30min to obtain negative electrode slurry with a solid content of 50%. The particle size of the negative electrode slurry is D 50 Meet the graphite particle size: Slurry D 50 ≤(graphite D 99 +Graphite D 50 ) / 2. Among them, slurry D50: 12.3 μm, negative electrode active material D99: 27.1 μm, negative electrode active material D50: 12.5 μm.
[0102] This embodiment discloses a negative electrode sheet for a sodium ion battery, including the negative electrode active layer (thickness of 170 μm) of this embodiment, specifically: the negative electrode slurry is evenly coated on the negative electrode collector copper foil (thickness of 8 μm), and then dried, cold pressed, and striped to obtain the negative electrode.
[0103] This embodiment discloses a sodium ion battery, including the negative electrode plate of this embodiment.
[0104] Example 2
[0105] The only difference between this embodiment and embodiment 1 is that when preparing the negative electrode slurry, NMP is used to replace the ethanol in embodiment 1 in the graphite treatment.
[0106] Example 3
[0107] The only difference between this embodiment and embodiment 1 is that when preparing the negative electrode slurry, this embodiment does not contain commercial SBR.
[0108] Example 4
[0109] The difference between this embodiment and embodiment 1 is that in this embodiment, the viscosity of the glue solution I is 500 mpa·s by adjusting the solvent water content in the glue solution.
[0110] Example 5
[0111] The difference between this embodiment and embodiment 1 is that in this embodiment, the viscosity of the glue solution I is 1000 mpa·s by adjusting the solvent water content in the glue solution.
[0112] Example 6
[0113] The difference between this embodiment and embodiment 1 is that in this embodiment, the viscosity of the glue solution I is 3500 mpa·s by adjusting the solvent water content in the glue solution.
[0114] Example 7
[0115] The difference between this embodiment and embodiment 1 is that in this embodiment, the viscosity of the glue solution I is 4000 mpa·s by adjusting the solvent water content in the glue solution.
[0116] Example 8
[0117] The difference between this embodiment and embodiment 1 is that in this embodiment, the viscosity of the glue solution II is 7000 mpa·s by adjusting the solvent water content in the glue solution.
[0118] Example 9
[0119] The difference between this embodiment and embodiment 1 is that in this embodiment, the viscosity of the glue solution II is 8000 mpa·s by adjusting the solvent water content in the glue solution.
[0120] Example 10
[0121] The difference between this embodiment and embodiment 1 is that in this embodiment, the viscosity of the glue solution II is 12000 mpa·s by adjusting the solvent water content in the glue solution.
[0122] Embodiment 11
[0123] The difference between this embodiment and embodiment 1 is that in this embodiment, the viscosity of the glue solution II is 13000 mpa·s by adjusting the solvent water content in the glue solution.
[0124] Example 12
[0125] The difference between this embodiment and embodiment 1 is that the degree of substitution Da of carboxymethyl cellulose in the glue solution I in this embodiment is 0.6.
[0126] 1) Alkalization: 0.5 kg of fiber was first mixed with 1 kg of ethanol, and soaked at 45° C. for 2 h. Then, 2 kg of 1 mol / L NaOH aqueous solution was added and reacted at 45° C. for 30 min to obtain an alkaline fiber solution.
[0127] 2) Etherification: 0.5 kg of chloroacetic acid was mixed with the alkalinized cellulose solution, and the mixture was reacted at 40° C. for 10 min to carry out an etherification reaction to generate carboxymethyl cellulose. Solvent water was added to the obtained glue system to obtain glue solution I. The mass fraction of carboxymethyl cellulose in glue solution I was about 2.2%, the degree of substitution Da of carboxymethyl cellulose was 0.60, and the viscosity was about 2000 mPa.s.
[0128] Embodiment 13
[0129] The difference between this embodiment and embodiment 1 is that the degree of substitution Da of carboxymethyl cellulose in the glue solution I in this embodiment is 0.8.
[0130] 1) Alkalization: 0.5 kg of fiber was first mixed with 1 kg of ethanol, and soaked at 45° C. for 2 h. Then, 2 kg of 1 mol / L NaOH aqueous solution was added and reacted at 45° C. for 30 min to obtain an alkaline fiber solution.
[0131] 2) Etherification: 0.5 kg of chloroacetic acid was mixed with the alkalinized cellulose solution, and the mixture was reacted at 45° C. for 25 min to carry out an etherification reaction to generate carboxymethyl cellulose. Solvent water was added to the obtained glue system to obtain glue solution I; wherein, the mass fraction of carboxymethyl cellulose in glue solution I was about 1.9%, the degree of substitution Da of carboxymethyl cellulose was 0.80, and the viscosity was about 2000 mPa.s.
[0132] Embodiment 14
[0133] The difference between this embodiment and embodiment 1 is that the degree of substitution Db of carboxymethyl cellulose in the glue solution II in this embodiment is 0.8.
[0134] 1) Alkalization: 0.5 kg of fiber was first mixed with 1 kg of ethanol, and then soaked at 45°C for 2 h. Then, 2 kg of 1 mol / L NaOH solution was added and reacted at 45°C for 30 min to obtain an alkaline fiber solution.
[0135] 2) Etherification: 0.5 kg of chloroacetic acid was mixed with the alkalinized cellulose solution, and the mixture was reacted at 55° C. for 30 min to carry out an etherification reaction to generate carboxymethyl cellulose. Solvent water was added to the obtained glue system to obtain glue II; wherein the mass fraction of carboxymethyl cellulose in glue II was about 1.1%, the degree of substitution Db of carboxymethyl cellulose was 0.80, and the viscosity was about 9000 mPa.s.
[0136] Embodiment 15
[0137] The difference between this embodiment and embodiment 1 is that the degree of substitution Db of carboxymethyl cellulose in the glue solution II in this embodiment is 1.2.
[0138] 1) Alkalization: 0.5 kg of fiber was first mixed with 1 kg of ethanol, and then soaked at 45°C for 2 h. Then, 2 kg of 1 mol / L NaOH solution was added and reacted at 45°C for 30 min to obtain an alkaline fiber solution.
[0139] 2) Etherification: 0.5 kg of chloroacetic acid was mixed with the alkalinized cellulose solution, and the mixture was reacted at 70° C. for 55 min to carry out an etherification reaction to generate carboxymethyl cellulose. Solvent water was added to the obtained glue system to obtain glue II; wherein the mass fraction of carboxymethyl cellulose in glue II was 0.8%, the degree of substitution Db of carboxymethyl cellulose was 1.20, and the viscosity was about 9000 mPa.s.
[0140] Example 16
[0141] The difference between this embodiment and embodiment 1 is that: in this embodiment, Db≠Da+0.3; Da is 0.6, and Db is 1.0.
[0142] Da is 0.6, and the preparation of glue solution I comprises:
[0143] 1) Alkalization: 0.5 kg of fiber was first mixed with 1 kg of ethanol, and soaked at 45° C. for 2 h. Then, 2 kg of 1 mol / L NaOH aqueous solution was added and reacted at 45° C. for 30 min to obtain an alkaline fiber solution.
[0144] 2) Etherification: 0.5 kg of chloroacetic acid was mixed with the alkalinized cellulose solution, and the mixture was reacted at 40° C. for 10 min to carry out an etherification reaction to generate carboxymethyl cellulose. Solvent water was added to the obtained glue system to obtain glue solution I; wherein the mass fraction of carboxymethyl cellulose in glue solution I was about 2.2%, the degree of substitution Da of carboxymethyl cellulose was 0.60, and the viscosity was about 2000 mPa.s.
[0145] Db is 1.0, preparation of glue solution II:
[0146] 1) Alkalization: 0.5 kg of fiber was first mixed with 1 kg of ethanol, and then soaked at 45°C for 2 h. Then, 2 kg of 1 mol / L NaOH solution was added and reacted at 45°C for 30 min to obtain an alkaline fiber solution.
[0147] 2) Etherification: 0.5 kg of chloroacetic acid was mixed with the alkalinized cellulose solution, and the mixture was reacted at 60° C. for 45 min to carry out an etherification reaction to generate carboxymethyl cellulose. Solvent water was added to the obtained glue system to obtain glue II; wherein the mass fraction of carboxymethyl cellulose in glue II was about 0.95%, the degree of substitution Db of carboxymethyl cellulose was 1.0, and the viscosity was about 9000 mPa.s.
[0148] Embodiment 17
[0149] The difference between this embodiment and embodiment 1 is that in the step of preparing the glue solution I in this embodiment, the mass fraction of carboxymethyl cellulose contained in the glue solution I is 1.5% by adjusting the original amount of fiber in the alkalization step.
[0150] Embodiment 18
[0151] The difference between this embodiment and embodiment 1 is that in the step of preparing the glue solution I in this embodiment, the mass fraction of carboxymethyl cellulose contained in the glue solution I is 3.5% by adjusting the original amount of fiber in the alkalization step.
[0152] Embodiment 19
[0153] The difference between this embodiment and embodiment 1 is that in the step of preparing the glue solution II in this embodiment, the mass fraction of carboxymethyl cellulose contained in the glue solution II is 0.5% by adjusting the original amount of fiber in the alkalization step.
[0154] Embodiment 20
[0155] The difference between this embodiment and embodiment 1 is that in the step of preparing the glue solution II in this embodiment, the mass fraction of carboxymethyl cellulose contained in the glue solution II is 1.4% by adjusting the original amount of fiber in the alkalization step.
[0156] Embodiment 21
[0157] The difference between this embodiment and embodiment 1 is that the mass ratio of ethanol aqueous solution to graphite in this embodiment is 0.05:100.
[0158] Embodiment 22
[0159] The difference between this embodiment and embodiment 1 is that the mass ratio of ethanol aqueous solution to graphite in this embodiment is 0.5:100.
[0160] Embodiment 23
[0161] The difference between this embodiment and embodiment 1 is that the concentration of ethanol in the ethanol aqueous solution in this embodiment is 0.01 mol / L.
[0162] Embodiment 24
[0163] The difference between this embodiment and embodiment 1 is that the slurry D in this embodiment 50 >(Graphite D 99 +Graphite D 50 ) / 2; wherein, slurry D 50 :20.3μm, graphite D 99 :27.1μm, graphite D 50 :12.5μm.
[0164] Comparative Example 1
[0165] The difference between this comparative example and Example 1 is that the glue liquid II is used in this comparative example instead of the glue liquid I in Example 1.
[0166] Comparative Example 2
[0167] The difference between this comparative example and Example 1 is that no ethanol aqueous solution is added in this comparative example.
[0168] Comparative Example 3
[0169] This comparative example discloses a negative electrode slurry for a sodium ion battery, which is different from Example 1 only in that an ethanol aqueous solution is used as the solvent of the negative electrode slurry in this comparative example.
[0170] The preparation of the negative electrode slurry (II) in this comparative example is as follows: the negative electrode slurry is prepared according to the following weight proportions: 95 parts of graphite, 1.5 parts of conductive agent, 0.8 parts of carboxymethyl cellulose, 1.2 parts of high viscosity binder, and 1.5 parts of commercial SBR, wherein the mass ratio of glue solution I to glue solution II is 5:5, and specifically comprises the following steps:
[0171] Stirring step: add graphite, conductive agent and glue solution I into 0.03 mol / L ethanol aqueous solution, stir for 90 min, and set the speed to 200 rpm.
[0172] Dispersion step: Add glue II, high viscosity binder, and appropriate amount of ethanol aqueous solution (concentration of 0.03 mol / L) to mixed material B, stir at 500 rpm for 30 minutes to obtain mixed material C, and finally add commercial SBR solution, stir at 200 rpm for 30 minutes to obtain negative electrode slurry with a solid content of 50%. The particle size of the negative electrode slurry is D 50 Meet the graphite particle size: slurry D 50 ≤(graphite D 99 +Graphite D 50 ) / 2. Among them, slurry D 50 :12.3μm, negative electrode active material D 99 :27.1μm, negative electrode active material D 50 :12.5μm.
[0173] The rest is the same as Example 1 and will not be described in detail.
[0174] Test example
[0175] This test example performs performance tests on the negative electrode slurries and batteries obtained in the examples and comparative examples, specifically including:
[0176] Test method:
[0177] 1. Use a laser particle size analyzer to test the particle size of the negative electrode slurry of the sodium ion battery after discharge;
[0178] 2. Fold the negative electrode sheet in half and record the material drop situation;
[0179] 3. Conductivity test: Use the probe method to test the film resistance of the prepared negative electrode; use a film resistance meter to test, take 1540.25mm 2 Place the small round negative electrode under the probe and press to test.
[0180] 4. Pole piece bonding strength: Use a 2.5 cm wide double-sided tape, stick one side to the negative pole piece and the other side to the glass plate, fix the glass plate, pull the pole piece with a tensile machine, and test the pole piece bonding strength;
[0181] Table 1
[0182]
[0183]
[0184] It can be seen from the above table that when only glue II is used in the dispersion step, the adhesion of the slurry is poor and the dispersibility of the slurry is poor; when the graphite is not pre-treated with a polar reagent, the dispersibility of the slurry is poor and the slurry particle fineness is large; as can be seen from Comparative Example 3, when a polar reagent is directly used as the solvent of the negative electrode slurry without pre-treating the graphite with a polar reagent, the aqueous binder and glue cannot be well soluble in such solvents, resulting in poor coating of the glue on the graphite and increased production costs.
[0185] If there is no special explanation, the actual meaning of "about" in the present invention is that the error is allowed within the range of ±2%, for example, about 100 is actually 100±2%×100. The "normal temperature" and "room temperature" in the present invention, if there is no special explanation, are about 20-30°C. The "between" in the present invention includes the number itself, for example, "between 2-3" includes the endpoint values 2 and 3.
[0186] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A sodium ion battery negative electrode slurry, characterized in that: The invention comprises a binder, a conductive agent, a glue and graphite treated with a polar reagent. The glue comprises a glue I and a glue II with different viscosities and both containing carboxymethyl cellulose.
2. The negative electrode slurry for sodium ion battery according to claim 1, characterized in that: Satisfies at least one of the following (1) to (5): (1) The viscosity of the glue solution I is 500 to 4000 mPa·s, and / or the viscosity of the glue solution II is 7000 to 13000 mPa·s; (2) The degree of substitution Da of carboxymethyl cellulose in the glue solution I and the degree of substitution Db of carboxymethyl cellulose in the glue solution II satisfy: Db = Da + 0.3; (3) The degree of substitution Da of carboxymethyl cellulose in the glue solution I is 0.6 to 0.8; and / or the degree of substitution Db of carboxymethyl cellulose in the glue solution II is 0.8 to 1.2; (4) In the negative electrode slurry, the mass ratio of the glue solution I to the glue solution II is (3-7):(3-7); (5) the mass fraction of carboxymethyl cellulose contained in the glue solution I is 1.5% to 3.5%, and / or the mass fraction of carboxymethyl cellulose contained in the glue solution II is 0.5% to 1.4%; (6) The polar reagent includes at least one of N-methylpyrrolidone and an alcohol reagent.
3. The negative electrode slurry for sodium ion battery according to claim 1, characterized in that: The polar reagent includes at least one of methanol, ethanol, propanol, butanol, pentanol or hexanol; And / or, the step of treating the graphite includes: mixing the graphite with a treatment solution containing a polar reagent to obtain the treated graphite; Preferably, the mass ratio of the treatment solution to graphite is (0.05-0.5):100; Preferably, in the treatment solution, the concentration of the polar reagent is 0.01-0.5 mol / L.
4. The negative electrode slurry for sodium ion battery according to claim 1, characterized in that: The adhesive comprises a high-viscosity adhesive, and the viscosity of the high-viscosity adhesive is 30000-80000 mpa.s; Preferably, the high-viscosity adhesive comprises a high-viscosity adhesive obtained by grafting and modifying polyethylene oxide; Preferably, the modified mass ratio of polyethylene oxide in the high-viscosity adhesive is 2% to 5%; Preferably, the molecular weight of the high viscosity adhesive is 20W-40W.
5. The negative electrode slurry for sodium ion battery according to claim 4, characterized in that: The high viscosity adhesive is prepared by a method comprising the following steps: S0, heating the acrylic acid aqueous solution, adding the initiator solution, reacting, and then adding polyethylene oxide, stirring to obtain a high-viscosity adhesive; Preferably, in the acrylic acid aqueous solution, the ratio of acrylic acid to water is (100-140) mg:12 mL; Preferably, in step S0, the heating temperature is 40-55° C., and the heating time is 0.5-4 h; Preferably, in step S0, the mass ratio of the acrylic acid aqueous solution to the initiator solution is (10-16):1, and the concentration of the initiator in the initiator solution is 0.2-3 mol / L; Preferably, in step S0, the reaction time is 0.5 to 5 hours; Preferably, in step S0, the molecular weight of polyethylene oxide is 3W to 15W.
6. The negative electrode slurry for sodium ion battery according to claim 1, characterized in that: The negative electrode slurry has a D 50 Particle size slurry D 50 And the particle size of graphite graphite D 99 Graphite D 50 The relationship is satisfied: slurry D 50 ≤(graphite D 99 +Graphite D 50 ) / 2.
7. A method for preparing a negative electrode slurry for a sodium ion battery according to claim 1, characterized in that: The steps include: S1, mixing raw graphite with a treatment solution containing a polar reagent to obtain a treated graphite slurry; S2, mixing the graphite slurry with a conductive agent, a glue, and a binder to obtain a negative electrode slurry for a sodium ion battery.
8. A sodium ion battery negative electrode active layer, characterized in that: Prepared by using the sodium ion battery negative electrode slurry according to any one of claims 1 to 6; Preferably, the thickness of the negative electrode active layer is 130-150 μm.
9. A negative electrode plate for a sodium ion battery, characterized in that: The sodium ion battery negative electrode active layer comprises the sodium ion battery negative electrode active layer as claimed in claim 8.
10. A sodium ion battery, characterized in that: Including the sodium ion battery negative electrode plate as described in claim 9.
Citation Information
Patent Citations
Method for producing electrode slurry for lithium ion secondary battery
CN101641812A
Preparation method of negative pole piece and application of prepared negative pole piece
CN102339989A
Preparation process for cathode paste of lithium-ion battery
CN102790218A
Sodium-ion battery negative electrode slurry preparation method and sodium-ion battery
CN116454233A
Self-emulsifying aqueous emulsion binder for silicon-based negative electrode of lithium ion battery and preparation method of self-emulsifying aqueous emulsion binder
CN117673360A